SUNDANESE DIALECT IN SINAR RESMI TRADITIONAL VILLAGE IN CISOLOK DISTRICT, SUKABUMI REGENCY: PHONOLOGICAL PERSPECTIVE - Thamrin, Husni; Isnendes, Retty (Jurnal Pendidikan Bahasa dan Sastra, 2020)
The main purpose of this study is to find out the similarities and differences in the form of speaking dialect intonation of Sirna Resmi tradisional society of Sukabumi Regency which is spoken by parents and young people. This study is conducted qualitatively with identification and classification in the form of Sundanese intonation of conversation dialect. Participants are two people with the age level of young (36 years old) and parents (69 years old). Data is collected by interview and record notes. Analysis of conversational dialect data is based on phonological theory of intonance referred to Katamba (1996). The first data is found with a number of intonations of conversational dialects from young people (36 years old) totaling 30 conversation sentences. From the data found three types of categories, namely; First intonation of downdrift tones is found in 2 types. Second, the tone of the downstep is found in 10 types. Third, the tone upstep is found in 18 types. In the second data, it was found that conversational dialect sentences of parents (69 years) amounted to 30 sentences of parents as elders in the Sinar Resmi village indigenous people. From the data that found three types of categories, namely; 1) Intonation of downdrift tones found 10 types. 2) Intonation of downstep tone found 11 types. 3) Intonation of upstep tones found 9 types.